An evaluation of a service to keep children safe in families with mental health and/or substance abuse issues. (October 2016) - Coates, Dominiek; Howe, Deborah
Objective: The objective of this study was to evaluate a specialised service designed to improve parenting capacity, child safety and family functioning in the context of parental mental health, drug and alcohol and child protection concerns. Method: Client data was collected over a period of 3 years and 3 months, including demographic characteristics, service usage, presenting issues and pre and post revised North Carolina Family Assessment Scale (NCFAS-G) scores. Results: A significant improvement between intake and discharge occurred on the majority of the 58 NCFAS-G subscale items (32/58). In particular, most significant change occurred in the domains 'family safety' ( p < 0.001) and 'family interactions' ( p < 0.001). Conclusion: Specialised programs can assist families with child safety concerns suffering from mental health and/or drug and alcohol problems.